Soradic ulcerative mutilating acropathy with imbalance of free amino acids in the cerebrospinal fluid. Issue 8 (August 1975) - Monaco, F; Riccio, A; Covacich, A; Durelli, L; Giordana, M T; Palmucci, L
Abstract : A case of sporadic ulcerative mutilating acropathy is described. Muscle biopsy showed signs of neurogenic atrophy. Motor nerve conduction velocity was slightly reduced. The muscles of the foot were completely unresponsive to electric stimulation of both femoral nerves. The content of free amino acids in serum and cerebrospinal fluid was determined by ion exchange chromatography, and compared with a control group. While in serum no significant changes were found, in CSF most amino acids showed great alterations, mainly consisting in an increase. It is suggested that the primary disturbance may be located in the spinal nerve roots.